A New Era of Black Box – Refreshed Approach via Latest Technologies and the Challenges - Z. M. Jawi; M. Z. A. Talib; F. A. A. Aziz; A. H. Ariffin; A. S. Salleh (Journal of the Society of Automotive Engineers Malaysia, 2022)
Generally used in aircraft to record and store operational data, the black box has also been used in road vehicles, either commercial or private, for safety, control, and investigative mechanism. Technological advancements have allowed the development of data-generating items in modern-day cars such as EDR and dashcams. Despite their benefits in road safety especially in vehicular forensics, there are concerns about safety, privacy, and users’ rights. This warrants refreshed approaches to gradually embed a digital culture into the existing automotive ecosystem. They include a collaborative effort to create an inclusive discussion among a group of local experts recognized as the Modern Vehicle Expert Consortium (MOVE), and a review of related laws and regulations to protect the end users, government, and related stakeholders.